2020
DOI: 10.1111/ics.12622
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive histological investigation of age‐related changes in dermal extracellular matrix and muscle fibers in the upper lip vermilion

Abstract: OBJECTIVE: Few histological studies have directly examined agerelated changes within the lips, although non-invasive investigations of such changes are increasing. Therefore, this study aimed to provide histological and molecular data on age-dependent alterations in the vermilion. METHODS: Upper vermilion specimens from 15 female Caucasian cadavers (age range, 27-78 years) were investigated histologically or immunohistochemically. RESULTS: Histologically, age-dependent decreases in areas occupied by hyaluronan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 40 publications
(64 reference statements)
0
2
0
Order By: Relevance
“…Changes have occurred in the composition of the dermis in the vermilion zone. Gomi et al 34 . also observed a reduction in signals for four proteins in the lip vermilion of older individuals compared to young individuals: hyaluronan synthase 1, procollagen type I, myosin heavy chain (MYH)2, and MYH7.…”
Section: Age‐related Changes In the Lip Vermilionmentioning
confidence: 92%
See 1 more Smart Citation
“…Changes have occurred in the composition of the dermis in the vermilion zone. Gomi et al 34 . also observed a reduction in signals for four proteins in the lip vermilion of older individuals compared to young individuals: hyaluronan synthase 1, procollagen type I, myosin heavy chain (MYH)2, and MYH7.…”
Section: Age‐related Changes In the Lip Vermilionmentioning
confidence: 92%
“…Changes have occurred in the composition of the dermis in the vermilion zone. Gomi et al 34 In terms of physiological parameters, with increasing age, there is an increase in lip hydration and a decrease in TEWL. 8 Tamura et al 35 showed that TEWL values for the lip declined until approximately 30 years of age.…”
Section: Ag E-rel Ated Chang E S In the Lip Vermilionmentioning
confidence: 99%